AsarFonts enriches Jawi writing application through technology - Muhammad Hafiz Aswad, Ahmad Kamal (Penerbit UMP, 2012)
AsarFonts is a technology-based product that is able to bring back the glory era of Jawi writing to the present day. In line with this aspiration, an official launching of the product was held on October 18 2012, in conjunction with the National-Level Jawi and Technology Seminar 2012 organised by Center of Modern Language and Human Sciences, Universiti Malaysia Pahang.